Election Integrity and Governance Challenges: Unravelling the Links between Voter Intimidation, Electoral Violence, Fraudulent Practices, and the Political Costs They Create in Indonesia - Yetty Sembiring; Afif Syarifudin Yahya (Universitas 17 Agustus 1945 Semarang, 2024)
Indonesia is one of the largest democratic countries in the world. Heads of Central dan Local government are elected through general elections, except for the Province of Yogyakarta. Even though general elections are a routine activity every five years, however there are still problems in its implementation. Through a qualitative examination of voter, election official, political candidate, and community leader interviews, this study explores issues with election integrity and governance in Indonesia. The study reveals the complex relationships that exist between electoral violence, voter intimidation, fraudulent activities, and the ensuing political consequences. Key themes that emerge include the regional nature of difficulties, the impact of political culture, resource restrictions, and the long-term societal costs. The results underscore the interdependence of these issues from various angles, highlighting the necessity of focused, cooperative actions. These observations add to the conversation on election integrity as Indonesia makes its way toward democracy and serves as a basis for the creation of policies and other initiatives that support democratic governance.